1983
DOI: 10.1038/305228a0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Ca2+-activated K+ channels under hormonal control in pig pancreas acinar cells

Abstract: Ca2+- and voltage-activated K+ channels are found in many electrically excitable cells and have an important role in regulating electrical activity. Recently, the large K+ channel has been found in the baso-lateral plasma membranes of salivary gland acinar cells, where it may be important in the regulation of salt transport. Using patch-clamp methods to record single-channel currents from excised fragments of baso-lateral acinar cell membranes in combination with current recordings from isolated single acinar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
106
2

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(118 citation statements)
references
References 9 publications
10
106
2
Order By: Relevance
“…The mechanisms underlying the Ca2+ influx are the subject of further investigation. MARUYAMA and PETERSEN (1984) suggested that the number of K+ channels per cell (N) increases 2-3 fold with CCK application in the pig pancreatic acinar cells, which has large K+ channels similar to those in the parotid gland acinar cells (MARUYAMA et al, 1983b). The value of N, estimated by ensemble fluctuation analysis, is about 30-110 (9 experimens), in the unstimulating parotid acinar cells (Maruyama et al, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the Ca2+ influx are the subject of further investigation. MARUYAMA and PETERSEN (1984) suggested that the number of K+ channels per cell (N) increases 2-3 fold with CCK application in the pig pancreatic acinar cells, which has large K+ channels similar to those in the parotid gland acinar cells (MARUYAMA et al, 1983b). The value of N, estimated by ensemble fluctuation analysis, is about 30-110 (9 experimens), in the unstimulating parotid acinar cells (Maruyama et al, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…In regards to pancreas, although we detected low levels of Lrrc26 message in pancreatic samples, we were unable to detect LRRC26 protein. Based on early recordings from pancreatic acinar cells (39,40) in which half activation of BK channels occurred at very negative voltages, we think it likely that LRRC26-containing BK channels are present in such cells, albeit at low current density. In fact, probably the best criterion for the presence of LRRC26-containing BK channels in a given cell type will rest on demonstration of appreciable fractional activation of BK channels at membrane potentials negative to 0 mV with 0 cytosolic Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, somatostatin inhibits both Ca 2ϩ -induced and cyclic AMP-induced amylase secretion [11][12][13][14], but in vitro, a few consistent effects on secretion have been described [13,15]. As for ionic fluid secretion from pancreatic acini, only one report concerns the effect of insulin on cation channel [16].Ca 2ϩ -activated K ϩ channels, which have been suggested to regulate the K ϩ permeability changes in plasma membrane during fluid secretion, have been identified on the basolateral membrane of Cl Ϫ -secreting pancreatic acinar cells in a variety of animal species [17][18][19][20]. It has been suggested that these K ϩ channels are important for Cl Ϫ uptake into cells [21].…”
mentioning
confidence: 99%
“…Ca 2ϩ -activated K ϩ channels, which have been suggested to regulate the K ϩ permeability changes in plasma membrane during fluid secretion, have been identified on the basolateral membrane of Cl Ϫ -secreting pancreatic acinar cells in a variety of animal species [17][18][19][20]. It has been suggested that these K ϩ channels are important for Cl Ϫ uptake into cells [21].…”
mentioning
confidence: 99%